(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2021)
In the light of the peaceful nuclear power plants (NPPs) project of the United Arab Emirates (UAE), the operation license has been issued and the first unit is being in commercial operation. This work deals mainly with radiological surveillance of the coastal boarder and some Islands of UAE as a baseline reference natural and artificial radioactivity mapping. Ultra-sensitive hyper pure Germanium (HpGe) detector was used to carry out the non-destructive gamma measurements. The area of study was divided into; Abu Dhabi region, northern emirates and islands. About 85 soils, shore sediment and water samples were collected based on the scientific sampling mechanism. The samples were analyzed for X-ray diffraction mineralogy (XRD). The radioactivity in Bq/kg of the natural 238U(226Ra), 232Th and 40K were calculated for all the collected samples. The artificial 137Cs was also observed in very low activity. The hazard indices were also calculated and found to be less than the recommended international and regional limits. The correlations between the measured radioisotopes were also depicted. The results were compared, presented and given in 3D histograms.